Religion and Critique – Jacques Ellul’s Concept in the Perspective of General Pedagogy - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
For general pedagogy, the concept of Jacques Ellul is an important example of solving the tension between religious and critical-emancipation engagement, which are usually involved in the theory of education in a separate way. We are able to give many examples of educational trends or ideologies that are within religious education and that dogmatically defend against criticism, as well as critical education, which in principle distrusts communities that are based on confessional devotion to religious principles and practices. Hence the Ellul’s concept that links Christianity and anarchy, from the perspective of general pedagogy is an important complement to its efforts to create a map of directions and currents of contemporary pedagogy.
Keywords: anarchy motorcycles; christianity; Jacques Ellul; general pedagogy; critical pedagogy; pedagogy of religion